Functional regression models: Some directions of future research. (February 2017) - Paganoni, Anna Maria; Sangalli, Laura M.
Abstract: We congratulate the authors for their excellent work that provides a clear overview of the large and now mature field of regression models for functional data. We here complement their discussion indicating some directions of further research that we deem particularly important.